Attaining the Health and Education Millennium Development Goals in Nepal - World Bank (Washington, DC, 2014)
This paper looks at Nepal's Millennium Development Goals (MDG) with respect to health and education. The paper is organized with part one dealing with education and is divided into three sections: section A details the current state of Nepal's MDG indicators and analyzes progress towards the goals; section B describes the policies that have contributed to Nepal's success, and policies that constrain its future achievements; and the final section C outlines the challenges facing Nepal in achieving the education MDGs. Part two of the paper deals with goals in health. This part of the paper also is divided into three sections with section A detailing health outcomes, progress and prospects; section B discusses the factors explaining progress in health and outcomes; and section C gives challenges for the future.